Research Trends in Career Choice: A Conceptual Review - Garg, Pratibha (International Journal of Psychosocial Rehabilitation, 2020)
India is rising at a very high speed and is envisioned to become a superpower soon. The productivity of the country contributes vastly towards this cause, and the productivity of a country is determined by the productivity of its citizens. The correct career choice amongst individuals determines to a large extent the productivity they will have in the future.Wide subject choices, the multiplicity of courses for students, the need for research in various career choices in different aspects cannot be overemphasized. The aim of this paper is to do research and recognize the patterns and trends in career choice amongst students. The paper aims to segregate the various factors affecting career choice as well as study their influence on students.